تعليم اللغة العربية باستخدام كتاب "حديثنا العربي" في مؤسسة تربية اللغة العربية سبلاك جومبانج - Ningsih, Sri Lestari Dian; Rohman, Fathur (EDUMALSYS Journal of Research in Education Management, 2023)
The textbook entitled "Haditsuna Al-‘arabi" is a textbook for elementary classes in the educational activities of the Splak Jombang Arabic Language Education Institute. There are differences in this textbook with other Arabic language textbooks. Because this book uses Indonesian in its teaching materials. Apart from focusing on textbooks, this study will discuss how to use these textbooks, and how to evaluate the results of using the book " Haditsuna Al-‘arabi ". The research methodology is a qualitative research with a qualitative descriptive approach, collecting data using document and interview methods, as well as observing data validity methods, including: Triangulation method. The results of this study can be summarized as follows: 1) Teaching Arabic at the Seblak Jombang Arabic Language Education Institute of four packages, the first package uses the book " Haditsuna Al-‘arobi ", the second package uses the book "Mukhtasor Jiddan", the third package uses the book "Kasyifatuss Saja”, the fourth package is accurate teaching or educational practices. Books and their translations into Indonesian. 3) The advantage of teaching Arabic using the book "Haditsuna al-‘arabi" is that the language used in this book is Indonesian, equipped with Arabic vocabulary in boxes, educational material in the form of stories and the book " Haditsuna al-‘arabi " is small. Weaknesses of teaching this is Arabic using the book " Haditsuna al-‘arabi "Most of the Arabic vocabulary is not done in the vocabulary box and the grammar rules are not recorded.